Timing of hospital admission in labour: latent versus active phase, mode of birth and intrapartum interventions: a correlational study - Rota, A.; Antolini, E.; Colciago, E.; Nespoli, Antonella; Borrelli, Sara E.; Fumagalli, Simona (Elsevier, 2018)
Background